Regulation of endothelial nitric-oxide synthase (NOS) S-glutathionylation by neuronal NOS: evidence of a functional interaction between myocardial constitutive NOS isoforms. - Idigo, W; Reilly, S; Zhang, M; Zhang, Y; Jayaram, R; Carnicer, R; Crabtree, M; Balligand, J; Casadei, B (American Society of Biochemistry and Molecular Biology, 2012)
Background PWhether neuronal nitric-oxide synthase (nNOS) plays a role in the endothelial NOS (eNOS)-dependent negative inotropic effect of β3-adrenergic stimulation remains to be established. Results nNOS knock-out or inhibition leads to increased superoxide production, eNOS uncoupling, and abrogation of β3-adrenergic responses. Conclusion Disabling nNOS disrupts eNOS function and downstream signaling. Significance nNOS plays a crucial role in preserving myocardial nitroso-redox balance and coupled eNOS activity.